Strategi Desain Dari Visual Branding The 6Th International Seminar on Nusantara Heritage (ISoNH) 2017 - I Kadek Dwi Noorwatha; I Gusti Ngurah Wirawan (Institut Seni Indonesia Denpasar, 2020)
This research is a qualitative descriptive study that examines the process of visual branding conceptualization from the 2017 ISoNH Seminar, whose significance is cross-cultural with a multidisciplinary approach. The stage of visual branding conceptualization can be divided into the stages of formulating a brand strategy, the stage of creative execution and the creative implementation stage. The results of the study indicate that ISoNh 2017's branding is an attempt to formulate the meaning of 'archipelago' as a regional identity as part of the creative design strategy of branding of an international seminar.